ANALISIS APLIKASI MANAJEMEN LAPORAN INVENTARISASI BARANG MASJID BERBASIS TEKNOLOGI INFORMASI ANDROID DENGAN PENINGKATAN MINAT MASYARAKAT TERHADAP INFAQ - Eka Puspita Zega (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
The management of mosque inventory is one of the crucial responsibilities that mosque administrators must undertake. Efficient inventory management in a mosque aids in understanding the condition of mosque items, identifying their needs, and effectively managing these assets. Presently, Android information technology has rapidly evolved and become an integral part of people's daily lives. This technology can be harnessed to develop an application for managing mosque inventory reports. The objective of this research is to analyze the impact of an Android-based information technology application for managing mosque inventory reports on increasing public interest in making donations (infak). This study employs a quantitative method using a survey approach. The research population comprises individuals who have previously made donations in mosques. The research sample consists of 100 randomly selected respondents. Data is collected through a questionnaire. The research findings demonstrate that the Android-based information technology application for managing mosque inventory reports has a positive and significant influence on increasing public interest in donations. This is evidenced by a regression coefficient value of 0.657, which is statistically significant (p < 0.05). Effective management of mosque inventory can enhance public trust in mosque administration. This is because the public gains transparent and accurate insights into the condition and needs of mosque items. Public trust in mosque management can boost interest in donations as people believe their donations will be used for the mosque's benefit. An Android-based information technology application for managing mosque inventory reports provides transparent and accurate information about the condition and requirements of mosque items. Therefore, this application can enhance public trust in mosque administration and further stimulate public interest in making donations.